Genome-Wide Characterization and Expression Analysis of HD-ZIP Gene Family in Dendrobium officinale - Yang, Qianyu; Xiang, Weibo; Li, Zhihui; Nian, Yuxin; Fu, Xiaoyun; Zhou, Guangzhu; Li, Linbao; Zhang, Jun; Huang, Guiyun; Han, Xiao; Xu, Lu; Bai, Xiao; et al. (Frontiers in Genetics, 2022)
The homeodomain-leucine zipper (HD-ZIP) gene family, as one of the plant-specific transcription factor families, plays an important role in regulating plant growth and development as well as in response to diverse stresses. Although it has been extensively characterized in many plants, the HD-ZIP family is not well-studied in Dendrobium officinale, a valuable ornamental and traditional Chinese medicinal herb. In this study, 37 HD-ZIP genes were identified in Dendrobium officinale (Dohdzs) through the in silico genome search method, and they were classified into four subfamilies based on phylogenetic analysis. Exon–intron structure and conserved protein domain analyses further supported the prediction with the same group sharing similar gene and protein structures. Furthermore, their expression patterns were investigated in nine various tissues and under cold stress based on RNA-seq datasets to obtain the tissue-specific and cold-responsive candidates. Finally, Dohdz5, Dohdz9, and Dohdz12 were selected to validate their expression through qRT-PCR analysis, and they displayed significantly differential expression under sudden chilling stress, suggesting they might be the key candidates underlying cold stress response. These findings will contribute to better understanding of the regulatory roles of the HD-ZIP family playing in cold stress and also will provide the vital targets for further functional studies of HD-ZIP genes in D. officinale.